STRATIGRAPHY COMPARTMENTALIZATION ANALYSIS OF AMALGAMATED CHANNELS RESERVOIRS; A CASE STUDY ON MF4 RESERVOIR IN PECIKO FIELD, KUTAI BASIN, EAST KALIMANTAN - Supriady
Peciko field is an offshore gas field located in Mahakam delta, East Kalimantan, Indonesia, covering around 350 km2 areas with 30 – 40 m water depth. This gas field is operated by international company Total (France) and Inpex (Japan). It was discovered in 1983 and had been produced since 1999. This giant gas field reached peak production around 1400 MMscfd in 2005. Peciko field has un-fault anticline structure with four way dip plunging to the south of the field. This field consists of multi-layered stacking reservoirs whitin 4500 m thick. The reservoirs are deposit at Late Miocene in fluvio-deltaic environments. Hydrocarbon reservoirs of Peciko field devided into two zones; Main Zone reservoirs located at 2100 – 4500 mSS depth which are dominated by Mouth bars sandstone deposit of delta front and Shallow Zone reservoirs at 500 – 2100 mSS depth dominated by channels sands deposit of delta plain and fluvial environments. Gas reservoirs of Main Zones had been produced since early phase of field development and currently the gas productions is declining. Recently, gas reservoirs of Shallow Zones are contributing around 40% of total field production to maintain the production decline. The main production contribution is coming from Y and MF4 channels reservoirs. The objective of this study is to perform stratigraphy compartementilizations analysis on MF4 channel reservoir which has contributed gas production until December 2016 higher then estimated Initial Gas In-Place (IGIP) that evaluated by previous study. MF4 reservoir is distributary channels sandstone deposited in the delta plain environment. At the late regression process of the one deltaic cycle, the progradation process generated amalgamated distributary channels in deltaic system and it caused stratigraphy compartementilizations. This stratigraphy compartementalization is thought to be reason why the actual gas - water contact of the recent drilled wells in platform S encountered deeper than actual contact of the produced wells in platform W area. However, depleted pressure test results found in these new S wells and the pressure data survey during production of platform W wells proved that the MF4 reservoirs is connected. v Detailed correlation and better understanding on sedimentology model when performed stratigraphy compartementilization analysis in these amalgamated channels becomes the key to answer the problematic of this study. This amalgamated distributary channels caused vertical and lateral connectivity in MF4 reservoir. The different actual contact between new drilled well in S platform and produced wells in W platform caused by existancy of possible barrier (shales) between amalgamated channels and overbank bars deposit between bifurcation distributary channels. This overbank bars deposit that has poor porosity and permeability quality caused the fluid flow to be slightly disturbed (semi-barrier) between bifurcation distributary channels. Based on this analysis, the geological model is reviewed by supporting new seismic attribute interpretation (inversion) that able to illustrate channel geometry distribution in 3-dimension. The integration of dynamic data (production cumulative and pressure data survey during production) is used as well to validate the more realistic volume of IGIP. This new geological model finally is expected to predict more accurate on production forcast and water break-through of MF4 reservoirs when performed dynamic reservoir simulations.